El paisaje protegido, pieza faltante en el Sistema de Áreas Protegidas de Colombia (2016)
Based upon the multiple dimensions of the landscape concept, and its recognition within the Colombian law system, we propose de category Protected Landscape for the National Protected Areas System. It is argued that the consideration of the protected landscape has the potential of contributing to conservation in lands in which biodiversity is linked with cultural practices, as well as to the national objective of conservation associated with the “social valuation of nature.” Several social and ecological criteria for the evaluation of potential sites as protected landscapes are thus presented, including regions and sites where they occur. A short discussion around the importance of integrating cultural and ecological values in protected areas conservation and strategies, as well as an agenda for further development and implementation, are presented.